Foraging Activity and Seasonal Food Preference of Linepithema micans (Hymenoptera: Formicidae), a Species Associated With the Spread of Eurhizococcus brasiliensis (Hemiptera: Margarodidae) - Nondillo, Aline [UNESP]; Ferrari, Leonardo; Lerin, Sabrina; Bueno, Odair Correa [UNESP]; Botton, Marcos (Entomological Soc Amer, 2014)
Linepithema micans (Forel) (Hymenoptera: Formicidae) is the main ant species responsible for the spread of Eurhizococcus brasiliensis (Wille) (Hemiptera: Margarodidae), a soil scale that damages vine plants in southern Brazil. The daily foraging activity of L. micans and its seasonal preference for protein-and carbohydrate-based foods were evaluated. The study was carried out in a greenhouse using seedlings of the Paulsen 1103 rootstock (Vitis berlandieri x Vitis rupestris) planted individually in pots and infested with colonies of L. micans. To determine the daily foraging activity and seasonal preference, a cricket (Gryllus sp.) and a 70% solution of inverted sugar and water were offered once a month for 12 mo. The ants foraging on each food source were counted hourly for 24 h. L. micans foraged from dusk until the end of the next morning, with higher intensity in the spring and summer. Workers of L. micans showed changes in food preference during the year, with a predominance of protein-based food during winter and spring and carbohydrate-based food during autumn. The implications of this behavior for control of the species with the use of toxic baits are discussed.
Keywords: grapevine; soil scale; daily foraging; seasonal preference